Evaluation of maximal aerobic velocity and prediction of performance in backstroke - Sano, S.; Bongbele, J.; Chatard, J. C.; Lavoie, J. M. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The functional and maximal aerobic power (FMAP) of approximately 200 swimmers (males and females) of different ages (11-12, 13-14, > 15 years) were evaluated using backstroke swimming according to a maximal multistage swim test recently developed (Lavoie et al., 1985). In addition, an estimate of the energy cost of swimming, the arm stroke index (ASI), i.e. the ratio of the number of arm strokes and swimming velocity, was measured. The results indicate a clear progression of both these variables with age. Using the best performance times produced by these swimmers, a regression equation for the prediction of performance times vas established, taking into account the following variables: FMAP, ASI, age, sex and the swimming distance. For the 100 and 200 m backstroke, the equation is: y = 1.08 + (0.033 FMAP) - (0.00044 ASI) - (0.019 sex) - (0.00082 distance), with a correlation coefficient of 0.8 and the standard error of estimate of 5.2%. These data can be used as a tool to partial out the swimming economy and energetic capacity in backstroke swimming.